ANALISIS PUTUSAN MK NO 13/PUU-XV/2017 TENTANG LARANGAN NIKAH DALAM SATU INSTANSI PERSPEKTIF MAQASHID AL-SYARI’AH - Fitriyani Fitriyani; Ro’fah Setyowati (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
The Decision of Constitutional Court No 13/PUU-XV/2017 caused change in the Chapter 153 A Paragraph (1) Letter F of UUK about the prohibition marriage terhadap the colleagues. But the problem, is The Decision of Constitutional Court has fulfilled citizen’s constitutional right. The research uses doctrinal approach.The specification of this study is descriptive analysis. The result of analysis indicate that consideration UUD NRI 1945 and human right bill permitting that rule, whereas UUP doesn’t regulate it. However, Islam doesn’t forbit this regulation exactly but conditionaly the time, place, and situation. Based on maqashid al-syari’ah approach indicated that constitutional court judge in his deciding matter not according to principle of maqashid al-syari’ah. Therefore, the Decision of Constitutional Court No 13/PUU-XV/2017 hasn’t fulfilled citizen’s constitutional right.